(untitled) (Edad Media. Revista de Historia, 2023)
During the 14th century, the county in Lemos became the county of Lemos. This process was marked by three main events. Firstly, when the local Castro family fell into disrepute, political figures from outside Lemos arrived in the area. Secondly, Pedro Fernández and his son Fernán Pérez, both of Castro lineage, saw the family regain its power. Thirdly, Pedro Enríquez de Castilla (nephew of the new king Enrique II) came to control the earldom after the civil war. The aim of this article is to analyse, wherever possible possible, the proportions and magnitude of the power held by the count in Lemos and throughout Galicia over the course of the whole century. We seek to understand the role played by the king in this process and to ascertain whether there is any relationship between political power and the territorial dominance of the counts of Lemos.